Key performance indicators for improving a CRM implementation - Fernandes, S. M. (2017)
This document analyses the main pros and cons factors in the implementation and configuration of instances of a Customer Relationship Management tool (CRM) in a company, with the purpose of understanding if the establishment of key performance indicators (KPIs) could help achieving a higher success rate in its implantation on a new business.